Effect of different breathing frequencies with breath-holding on muscle activity and coordination during butterfly swimming in national-level female swimmers - Yamakawa, Keisuke Kobayashi; Sengoku, Yasuo; Takagi, Hideki (Frontiers in Sports and Active Living, 2025)
The aim of this study was to clarify the effect of different breathing frequencies with breath-holding on muscle activity and coordination during butterfly swimming in competitive swimmers. Eight national-level female swimmers participated in this study. They performed 25-m maximal butterfly swims with two breathing frequencies (task 1: swimming with the frontal breathing action for every stroke, and task 2: swimming while alternating the cycles with frontal breathing action and with breath-holding). From these tasks, the three different cycles (breathing cycle in task 1, breathing and breath-holding cycles in task 2) were analyzed. Surface electromyography was measured from 12 muscles of the right upper and lower limb, and trunk. A nonnegative factorization algorithm was used for muscle synergy analysis from the electromyographic data. Our results showed the activity timing for Triceps brachii, Deltoideus anterior, Latissimus dorsi, Biceps femoris and Gastrocnemius became earlier in the breath-holding cycle compared to those in the breathing cycle of task 1. However, the activity timing of all the muscles did not change between the breathing and breath-holding cycles of task 2. The number of muscle synergies was the same across the three cycles, except for one swimmer. The muscle combination of all the synergies was very similar across the three cycles. In contrast, the drive timing of the two synergies, which relate to the arm-pull movement and the first and second upward kicks, respectively, became earlier in the breath-holding cycle compared to those in the breathing cycle of task 1, while the drive timing did not change between the breathing and breath-holding cycles of task 2. These results suggest that the temporal characteristics of muscle activity and synergies are more influenced by different breathing frequencies than by frontal breathing action. Therefore, researchers should consider these effects when analyzing muscle activity during butterfly swimming.